Deep learning game agents in Bomberland: A comparative analysis (2025)
Bomberland is a modified clone of the popular arcade game Bomberman developed for an AI Agent Competition, adding a layer of cooperation using teams. This project aims to highlight how popular Deep Learning algorithms for game agents, Deep Q Learning and NEAT, perform against added complexity through cooperative, adversarial, and stochastic elements.